Distribution and degradation of terrestrial organic matter in the sediments of peat-draining rivers, Sarawak, Malaysian Borneo - Ying, Wu; Kun, Zhu; Jing, Zhang; Moritz, Müller; Shan, Jiang; Aazani, Mujahid; Mohd Fakharuddin, Muhamad; Sien, Edwin Aun Sia (Copernicus Publications, 2019)
Tropical peatlands are one of the largest pools of terrestrial organic carbon (OCterr); however, our understanding of the dynamics of OCterr in peat-draining rivers remains limited, especially in Southeast Asia. This study used bulk parameters and lignin phenol concentrations to investigate the characteristics of OCterr in a tropical peat-draining river system (the main channel of the Rajang and three smaller rivers: the Maludam, Simunjan, and Sebuyau) in the western part of Sarawak, Malaysian Borneo. The depleted δ 13C levels and lignin composition of the organic matter indicates that the most important plant source of the organic matter in these rivers is woody angiosperm C3 plants, especially in the three small rivers sampled. The diagenetic indicator ratio, i.e., the ratio of acid to aldehyde of vanillyl phenols ((Ad/Al)V), increased with decreasing mean grain size of sediment from the small rivers. The selective sorption of acid relative to aldehyde phenols might explain the variations in the (Ad/Al)V ratio. Elevated (Ad/Al)V values observed from the Maludam’s sediments may also be attributed to source plant variations. The (Ad/Al)V ratio appears to be related to the C/N ratio (the ratio of total organic carbon to total nitrogen) in the Rajang and small rivers. In small rivers, a quick decline of C/N ratios is a response to the slower modification of (Ad/Al)V ratios due to better preservation of lignin phenols. An accumulation of lignin phenols with higher total nitrogen percentages (TN%) in the studied systems was observed. Most of the OCterr discharged from the Rajang and small river systems was material derived from woody angiosperm plants with limited diagenetic alteration before deposition and thus could potentially provide significant carbon to the atmosphere after degradation.